Prostate Cancer Morbidity And Mortality Among Men In High-Risk Areas - Rizаev J. A.; Rahimov N. M.; Kadirov Х. Х.; Shaxanova Sh. Sh. (Genius Journals, 2023)
Prostate cancer is the second most common cancer among cancers in men worldwide and the fifth leading cause of death. Prostate cancer can be asymptomatic at an early stage and therefore often requires only active surveillance. According to GLOBOCAN 2018, there were 1,276,106 new cases of prostate cancer worldwide in 2018, with awareness rates among these figures being higher in developed countries. Differences in incidence rates worldwide reflect differences in the use of diagnostic tests
Keywords: prostate cancer; high-risk areas; men; mortality rates